2012
DOI: 10.1007/s00256-011-1347-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cyclops lesions after different anterior cruciate ligament reconstructions: a comparison of the single-bundle and remnant bundle preservation techniques

Abstract: The prevalence of a cyclops lesion was similar in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…Previous studies have demonstrated a good sensitivity, specificity, and accuracy of MRI in revealing cyclops lesions (sensitivity 85.0%, specificity 84.6%, and accuracy 84.8%) [24,25]. In all mentioned previous studies the prevalence and clinical relevance of cyclops lesions have only been assessed in subjects which presented with severe loss ofknee extension at follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated a good sensitivity, specificity, and accuracy of MRI in revealing cyclops lesions (sensitivity 85.0%, specificity 84.6%, and accuracy 84.8%) [24,25]. In all mentioned previous studies the prevalence and clinical relevance of cyclops lesions have only been assessed in subjects which presented with severe loss ofknee extension at follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…An increased incidence of cyclops lesions was not observed (Cha et al 2012). However, long-term results are missing and clinical studies comparing the remnant preservation technique with ACL reconstruction without remnant preservation are lacking.…”
Section: Remnant Augmentationmentioning
confidence: 92%
“…An advantage of an isolated reconstruction of the AM or PL bundle might be preservation of proprioceptive elements within the remnant (Cha et al 2012;Kazusa et al 2013). Moreover, in many cases, a gracilis tendon graft is strong enough to reconstruct one torn bundle.…”
Section: Isolated Reconstruction Of a Torn Bundlementioning
confidence: 98%
See 1 more Smart Citation
“…Cyclops lesions were defined as soft tissue masses with a convex anterior border located in the intercondylar notch, characterized by varying signal intensities on intermediate‐weighted images (3D FSE), as previously described . Previous studies have demonstrated a good sensitivity, specificity, and accuracy of MRI in revealing cyclops lesions (sensitivity 85.0%, specificity 84.6%, and accuracy 84.8%) . In addition, a diameter of 5 mm in each plane was used as the minimum required size to avoid false‐positive cases …”
Section: Methodsmentioning
confidence: 99%